(3bUGFO ef GdedMhfs - (3GdJgGej GdeOZQjs
(3ChdgG (B:s
(3jG SYOfG jG HTQi HhLhO gPG GdSGbj s
(3BNQgG (B:s
(3YTbJge aSHhfj dG JMSH GdYTb SgdkG s
(3bWYI efgGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B5 - (3U (B107 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs